In the Kingdom of the Ditch - Davis, Todd (Book collections on Project MUSE., 2013)
The author maps the mysterious arc between birth and death, celebrating the beauty and pain of our varied entrances and exits, while taking readers into the deep forests and waterways of the northeastern United States. With an acute sensibility for language unlike any other working poet, the author captures the nuances in the flowers, trees, and animals he encounters through a daily life spent in the field. The author draws upon stories and myths from Christian, Transcendental, and Buddhist traditions to explore the intricacies of the spiritual and physical world we too often overlook. In celebrating the abundant life he finds in a ditch replete with Queen Anne's lace and milkweed, raspberries and blackberries, goldenrod and daisies, the poet suggests that life is consistently transformed, resurrected by what grows out of the fecundity of our dying bodies. In his fourth collection, he provides not only a taxonomy of the flora and fauna of his native Pennsylvania, but also a new way of speaking about the sacred walk we make with those we love toward the ultimate mystery of death.